OBSERVATIONS ON THE FOOD AND FEEDING HABITS OF THE EEL, MURAENESOX CINEREUS (FORSKAL) FROM PORTO NOVO - Devadoss, P; Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Feeding in Muraenesox cinereus was studied from the catches of hooks andline fishing operations from^ the catamarans. This fish is a carnivore and largelypiscivorous, feeding on the pelagic, demersal and bottom living organisms. Cannibalistictendency is noticed. Pelagic fishes like the mackerel and the clupeids arefound mostly preferred.